Characterizing profiles of polysubstance use among high school students in Baltimore, Maryland: A latent class analysis. (1st June 2020) - Schneider, Kristin E.; Brighthaupt, Sherri-Chanelle; Winiker, Abigail K.; Johnson, Renee M.; Musci, Rashelle J.; Linton, Sabriya L.
Highlights: Polysubstance use was common among adolescents who used drugs in Baltimore City. Three profiles emerged: alcohol/marijuana, polysubstance, and alcohol/inhalants/pain medication. The polysubstance use class was more commonly male and 66 % had injected drugs. Abstract: Background: Adolescent drug use has long term health consequences, like substance use disorders and psychiatric illnesses. Proximal health risks, especially for overdose, are amplified when multiple substances are combined. Existing literature on polysubstance use among adolescents has largely focused on alcohol, tobacco, and marijuana, but has largely excluded other drugs like opioids. Understanding how adolescents combine illicit drugs is essential for intervening to prevent poor health outcomes. Methods: We aimed to explore patterns of lifetime polysubstance use among adolescents in Baltimore City. We used data on 9th-12th graders recruited to participate in the 2017 local Baltimore Youth Risk Behavior Survey who reported any lifetime drug use (n = 387; 60 % female, 77 % non-Hispanic Black). We then conducted a latent class analysis using 10 indicators of lifetime drug and alcohol use. After selecting the class model, we tested for associations between the class profiles and race, sex, school grade, and lifetime injection drug use. Results: We identified three profiles of lifetime polysubstance use in our sample: alcohol and marijuana (68.6 % of sample), polysubstance (22.0 %), and alcohol/pain medication/inhalant use (9.4 %). Members of the polysubstance use class were more likely to be male and to report injection drug use. Conclusions: Understanding broader patterns of drug use beyond alcohol, tobacco and marijuana among adolescents is a crucial step towards preventing adverse drug and health-related outcomes later in life. More research is needed to characterize the full health impact of youth polysubstance use patterns and related risk behaviors like injection drug use.